Climate & Gig Work: Is Heat Wave Reducing Gig Riders' Productivity in Greater Jakarta? - Apriliawan, Yohanes Eki (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
This study demonstrates that rising surface temperatures significantly reduce gig rider productivity in Greater Jakarta, primarily by decreasing their weekly working hours and monthly income. Using spatial panel analysis with socioeconomic and environmental data from 2021 to 2024, we find that heat impacts are most severe in densely built, low-vegetation areas, while green spaces offer mitigation. Vegetation buffers the negative effects of heat, whereas higher night-time economic intensity exacerbates them. Metropolitan-scale analysis reveals that increases in temperature in one area also depress productivity in neighboring areas, highlighting interconnected climate risks. Further, gig riders are especially vulnerable compared to non-gig informal workers due to their mobility, exposure, and limited protections. These findings directly support policy priorities on human capital, economic transformation, and climate adaptation, emphasizing the urgent need for urban heat-safety standards, cooling infrastructure, and adaptive social protection for gig workers.